The right stuff? Personality and entrepreneurship - Barton Hughes Hamilton; Nicholas W. Papageorge; Nidhi Pande (Quantitative Economics, 2019)
We construct a structural model of entry into self-employment to evaluate the impact of policies supporting entrepreneurship. Previous work has recognized that workers may opt for self-employment due to the nonpecuniary benefits of running a business and not necessarily because they are good at it. Other literature has examined how socio-emotional skills, such as personality traits, affect selection into self-employment. We link these two lines of inquiry. The model we estimate captures three factors that affect selection into self-employment: credit constraints, relative earnings, and preferences. We incorporate personality traits by allowing them to affect sector-specific earnings as well as preferences. The estimated model reveals that the personality traits that make entrepreneurship profitable are not always the same traits driving people to open a business. This has important consequences for entrepreneurship policies. For example, subsidies for small businesses do not attract talented-but-reluctant entrepreneurs, but instead attract individuals with personality traits associated with strong preferences for running a business and low-quality business ideas.
Keywords: J23; J24; J31; J32; 330; Entrepreneurship; personality; socioemotional skills; latent factors